2019
DOI: 10.1016/j.socscimed.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterning, correlates, and inequality in suicide across 432 neighborhoods in Taipei City, Taiwan

Abstract: More than half of the world's population now lives in urban areas. Understanding the spatial distribution of suicide in these settings may inform prevention. Previous analyses of the spatial distribution of suicide in cities were mostly restricted to Western nations. We investigated the spatial pattern of suicide and factors associated with its spatial distribution in Taipei City, Taiwan. We estimated smoothed standardized mortality ratios for overall suicide and suicide by sex/age group across 432 neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 49 publications
7
32
1
Order By: Relevance
“…In Hong Kong, higher suicide clusters were mainly found in the New Territories where the population density was low . This pattern is consistent with the findings in China, Japan, and Taiwan where the higher rates of elderly suicide were found to be higher in the rural areas . Contributors to the higher rate of elderly suicide in the lower‐density population areas include social isolation, lack of services, physical disconnectedness, stigma toward mental disorder, and concentration of the minority groups.…”
Section: Discussionsupporting
confidence: 85%
“…In Hong Kong, higher suicide clusters were mainly found in the New Territories where the population density was low . This pattern is consistent with the findings in China, Japan, and Taiwan where the higher rates of elderly suicide were found to be higher in the rural areas . Contributors to the higher rate of elderly suicide in the lower‐density population areas include social isolation, lack of services, physical disconnectedness, stigma toward mental disorder, and concentration of the minority groups.…”
Section: Discussionsupporting
confidence: 85%
“…We found similar spatial patterning of self-harm across sex/age groups except the elderly group, which showed no obvious spatial patterning. A few previous studies that investigated sex- and age-specific spatial patterning of suicide similarly showed a higher degree of spatial variations in younger than older groups (Chang et al ., 2011; Lin et al ., 2019). Our regression analyses suggested that younger people living in areas characterised by high levels of unemployment, limiting longstanding illness, lone-parent households and White-British ethnicity had higher rates of self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding socio-economic factors associated with area-speci c suicide risk, it has been pointed out that ndings from Asian countries may be different from those of Western countries. 15 The results from the UK tended to show that area-speci c suicide risk was more strongly associated with social fragmentation than socioeconomic deprivation. 11,12,14,16,17 In contrast, studies from Taiwan and Hong Kong have shown that indicators of socioeconomic deprivation appear to affect area-speci c suicide risk as strong or stronger than those of social fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,14,16,17 In contrast, studies from Taiwan and Hong Kong have shown that indicators of socioeconomic deprivation appear to affect area-speci c suicide risk as strong or stronger than those of social fragmentation. 3,15,18 Although it is not clear why the ndings of Asian countries are different from those of the UK, Lin et al suggested that one of the reasons may be the differences in social protection measures between the UK and Asian countries. 15 That is, social protection measures might be relatively more comprehensive in the UK than in Asian countries and offset some of the suicide risk in deprived areas.…”
Section: Introductionmentioning
confidence: 99%